2020
DOI: 10.1097/sla.0000000000004529
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Intraoperative Laser Fluorescence Angiography With Indocyanine Green Predicts Early Graft Function After Kidney Transplantation

Abstract: Objective: This study was designed to demonstrate the predictive ability of quantitative indocyanine green (ICG) fluorescence angiography for the short-term postoperative outcome, the occurrence of delayed graft function (DGF), and long-term graft survival. Summary Background Data: DGF is a relevant problem after kidney transplantation; sufficient microperfusion of the allograft is crucial for postoperative organ function. Fluorescence angiography with ICG can serve as an intraoperative quality control of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…In view of the good performance of the five-mRNAbased risk score for DGF prediction, this model may provide necessary guidance for early posttransplant or even pretransplant decision-making in DCD KT. On the one hand, transcription analysis of 1-hour renal biopsy by microarray or qPCR may provide timely warning of the risk of DGF immediately after DCD KT, which could promote timely therapeutic or preventive interventions to minimize the impact of DGF on KT recipients, including the close monitoring strategy, the adjustment of immunosuppressive regimen, the optimization of volume management and the administration of thymoglobulin (26,32). Meanwhile, patients with lower DGF risk may benefit from a shorter intensive monitoring period, therefore resulting in shorter overall hospital stays and lower medical costs (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the good performance of the five-mRNAbased risk score for DGF prediction, this model may provide necessary guidance for early posttransplant or even pretransplant decision-making in DCD KT. On the one hand, transcription analysis of 1-hour renal biopsy by microarray or qPCR may provide timely warning of the risk of DGF immediately after DCD KT, which could promote timely therapeutic or preventive interventions to minimize the impact of DGF on KT recipients, including the close monitoring strategy, the adjustment of immunosuppressive regimen, the optimization of volume management and the administration of thymoglobulin (26,32). Meanwhile, patients with lower DGF risk may benefit from a shorter intensive monitoring period, therefore resulting in shorter overall hospital stays and lower medical costs (32).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, transcription analysis of 1-hour renal biopsy by microarray or qPCR may provide timely warning of the risk of DGF immediately after DCD KT, which could promote timely therapeutic or preventive interventions to minimize the impact of DGF on KT recipients, including the close monitoring strategy, the adjustment of immunosuppressive regimen, the optimization of volume management and the administration of thymoglobulin (26,32). Meanwhile, patients with lower DGF risk may benefit from a shorter intensive monitoring period, therefore resulting in shorter overall hospital stays and lower medical costs (32). However, it is worth noting that the timeliness of gene expression quantification is key to the utility of the genomic model in clinical practice, which relies on the further development of rapid nucleic acid quantification technology and the optimization of whole processes of gene detection, including specimen collection and preparation, nucleic acid quantification and results return (33).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that the impairment of intraoperative microperfusion in the allograft cortex is a risk factor for the occurrence of DGF, and that ICG Ingress is an independent predictor of DGF. Further studies are warranted to analyse the effect of applying early therapeutic approaches to prevent DGF in kidney transplant recipients, thus improving long-term graft success [46]. The use of imaging techniques to diagnose post-renal transplant complications has been discussed extensively in recent reviews [47][48][49]; therefore, the present work will only examine a few of the most recent studies in this field.…”
Section: Imagingmentioning
confidence: 99%
“…In brief, a bolus of ICG is injected into the patient intravenously, NIR light is then absorbed by ICG in the tissue, and the resulting fluorescence is a reflection of perfusion. After the introduction of ICG angiography in clinical practice in 1989 to evaluate choroidal circulation[ 14 ], fluorescence imaging technology has been used in hepatobiliary[ 15 , 16 ], gastric cancer[ 17 ], gynecologic cancer[ 18 ], breast cancer[ 19 ] and transplantation surgery[ 20 ]. Furthermore, many colorectal surgeons routinely use ICG imaging to assess bowel viability during colorectal anastomosis.…”
Section: Introductionmentioning
confidence: 99%